Purple teaming in system hacking - Karhunen, Eetu (My University, 2025)
The cybersecurity world is in a continuous battle with hostile adversaries. In order to keep computer systems safe from breaches, the approaches of cybersecurity professionals need to evolve faster than the adversaries who are trying to find vulnerabilities inside the systems in order to steal data. The problem that the field of cybersecurity faces in a system hacking concept is that the traditional approaches that have been implemented into the industry might not be the most efficient ones. The traditional red and blue teaming doesn’t use communication in the most efficient way. Finding the best approach to defending an organization’s assets is crucial. This thesis explores what is ethical hacking and how it has been imported into organizations cybersecurity training by using red and blue team simulations. Lastly, this thesis compares red and blue teaming against purple teaming. Purple teaming is a new approach to improving system security that can be an upgrade to defending against hostile adversaries. Purple teaming introduces enhanced communication to the red and blue team simulations and it can be implemented into organizations that don’t have enough capital for red and blue teaming.
Keywords: Ethical Hacking, Cybersecurity, System Hacking, Cyber Kill Chain, Operating Systems, Red team, Blue team, Purple team